EFISIENSI PEMASARAN KACANG METE (CASHEW NUTS) DI KABUPATEN GUNUNG KIDUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA (PENDEKATAN ANALISIS EFISIENSI OPERASIONAL MARK-UP PENJUALAN) - Budiarto Budiarto (Jurnal Dinamika Sosial Ekonomi, 2007)
The objective of this research is to identity the efficiency of the Cashew Nuts distribution in the two sample areas, namely sub district Semin and Semanu Gunung Kidul distric. The research method is descripfif The parameters used in the research are ; 1) profit margin and marketing margin and 2) mark-up analysis (i.e.mark-up on selling).  Several Informaition resulted from the research are as follows : (1) there are four pattern of the distributon namely, a) pattern farmer producer-collector I- consumer b). pattern 2 : farmer producer- collector I – collector II - consumer c). pattern 3 - : farmer producer - colleetor I -retailer – consumer d) pattern - 4 : farmer producer- collector I – collector II – retailer – consumer (2) marketing efficency value are : a). marketing margin value for each pattern are ; pattern 1 Rp 24.389,25/kg, pattern 2 Rp 24.389,25/kg, pattern 3 Rp 26,379,25,/kg, pattern 4 Rp 26.379,25/kg b) profit value and margin collector I pattern Rp 8.847,08 (65,49%), pattern II Rp 6.398,65 (62,63%), pattern III Rp 5.473,68(40,52%), and pattern IV Rp 6.398,65 (47,36%), c). we conclude that operational efficiency of all Pattern using  above method is generally high. Eventually we conclude that the distribution system of cashew nuts in Gunung Kidul district is efficient.Keywords : cashew nut , margin, efficiency